Distinguishing Patients With Distant Metastatic Differentiated Thyroid Cancer Who Biochemically Benefit From Next Radioiodine Treatment - Sa, Ri; Cheng, Lin; Jin, Yuchen; Fu, Hao; Shen, Yan; Chen, Libo (Frontiers in Endocrinology, 2020)
ABSTRACT Background: Repeated radioiodine (131I) treatment (RT) are commonly performed in patients with 131I-avid distant metastatic differentiated thyroid cancer (DM-DTC), but more precise indications remain indeterminate. This prospective study was conducted to explore predictors for biochemical response (BR) to next RT. Methods: Totally thyroidectomized patients with 131I-avid DM-DTC demonstrated by initial post-therapeutic whole body scan (Rx-WBS) were consecutively recruited. Repeated RTs were performed at a fixed dose and a fixed interval, which was terminated once a decline in thyroid stimulating hormone-suppressed thyroglobulin (Tgon) could not be achieved or Rx-WBS was negative. BR was evaluated by change rate of Tgon level (∆Tgon%). Results: After exclusion of 27 ineligible courses, a total of 166 neighboring course pairs from 77 patients were established and utilized. Univariate and multivariate analyses showed that the maximum target/background ratio (T/Bmax) on the whole body scan and ∆Tgon% derived from the former RT were independently associated to the latter one. In predicting biochemical remission, the positive predictive value (PPV) and negative predictive value (NPV) of T/Bmax at the cut-off value of 8.1 were 79.1% and 84.0%, respectively; whereas the PPV and NPV of ∆Tgon% at the cut-off value of 25.3% were 70.8% and 77.1%, respectively. Notably, the PPV of combined T/Bmax ≥ 8.1 and ∆Tgon% ≥ 25.3% increased to 87.7%; while the NPV of T/Bmax ≥ 8.1 or ∆Tgon% ≥ 25.3% reached as high as 97.7%. Conclusions: This study revealed that combined use of the latest RT-derived T/Bmax and ∆Tgon% may efficiently identify biochemical responders/non-responders to next RT, warranting management optimization of patients with 131I-avid DM-DTC.